Molecular Signatures of Non-typeable Haemophilus influenzae Lung Adaptation in Pediatric Chronic Lung Disease - Aziz, Ammar; Sarovich, Derek S.; Nosworthy, Elizabeth; Beissbarth, Jemima; Chang, Anne B.; Smith-Vaughan, Heidi; Price, Erin P.; Harris, Tegan M. (Frontiers in Microbiology, 2019)
Non-typeable Haemophilus influenzae (NTHi), an opportunistic pathogen of the upper airways of healthy children, can infect the lower airways, driving chronic lung disease. However, the molecular basis underpinning NTHi transition from a commensal to a pathogen is not clearly understood. Here, we performed comparative genomic and transcriptomic analyses of 12 paired, isogenic NTHi strains, isolated from the nasopharynx (NP) and bronchoalveolar lavage (BAL) of 11 children with chronic lung disease, to identify convergent molecular signatures associated with lung adaptation. Comparative genomic analyses of the 12 NP-BAL pairs demonstrated that five were genetically identical, with the remaining seven differing by only 1 to 3 mutations. Within-patient transcriptomic analyses identified between 2 and 58 differentially expressed genes in 8 of the 12 NP-BAL pairs, including pairs with no observable genomic changes. Whilst no convergence was observed at the gene level, functional enrichment analysis revealed significant under-representation of differentially expressed genes belonging to Coenzyme metabolism, Function unknown, Translation, ribosomal structure and biogenesis Cluster of Orthologous Groups categories. In contrast, Carbohydrate transport and metabolism, Cell motility and secretion, Intracellular trafficking and secretion, and Energy production categories were over-represented. This observed trend amongst genetically-unrelated NTHi strains provides evidence of convergent transcriptional adaptation of NTHi to paediatric airways that deserves further exploration. Understanding the pathoadaptative mechanisms that NTHi employs to infect and persist in the lower paediatric airways is essential for devising targeted diagnostics and treatments aimed at minimising disease severity, and ultimately, preventing NTHi lung infections and subsequent chronic lung disease in children.